The Influence of Service Quality and Brand Image on Customer Satisfaction: Study on One of The Fast-Food Restaurants in Bandung - Kusuma, Alvina Faradila; Juhana, Dudung; Zulfikar, Vicky Achmad; Purana, R. Deni; Suswanto, Djadjat (Journal of Economics, Management, and Entrepreneurship, 2024)
This study sought to evaluate the influence of Service Quality and Brand Image on Customer Satisfaction at a fast-food restaurant in Bandung. This study utilizes a quantitative methodology with multiple linear regression techniques (path analysis) to investigate the relationships among variables. The research sample was obtained using the Slovin method, resulting in 84 participants from the restaurant's clientele. Data was collected using a Likert scale questionnaire to evaluate respondents' perceptions of service quality, brand image, and customer satisfaction. The data were analyzed using SPSS software version 23.0 to evaluate validity, reliability, and inter-variable correlations in this study. The results revealed that the average total Service Quality was 2.70, classifying it as "Quite Good." Brand Image has an average score of 2.72, categorizing it as "Quite Good." The average Customer Satisfaction is 2.65, categorized as "Quite Good." Subsequent statistical analysis reveals that Service Quality significantly impacts Customer Satisfaction, suggesting that enhancements in service quality are associated with elevated levels of customer satisfaction. Brand Image significantly impacts Customer satisfaction, indicating that a more positive brand image in customers' perceptions is associated with higher satisfaction with the restaurant. A further analysis indicates that the Correlation Coefficient is 0.546, showing a moderately strong relationship between Service Quality and Brand Customer Satisfaction. The direct effect of Service Quality and Brand Image on Customer Satisfaction is 0.143, while the indirect effect is 0.327, yielding a cumulative effect of 0.470. Thus, both Service Quality and Brand Image substantially affect Customer Satisfaction in the fast-food outlets analyzed. This suggests that to improve customer satisfaction, restaurants must raise service quality and strengthen their brand image to align with consumer expectations.